2020
DOI: 10.3390/sports8090125
|View full text |Cite
|
Sign up to set email alerts
|

Tapering and Peaking Maximal Strength for Powerlifting Performance: A Review

Abstract: Prior to major competitions, athletes often use a peaking protocol such as tapering or training cessation to improve performance. The majority of the current literature has focused on endurance-based sports such as swimming, cycling, and running to better understand how and when to taper or use training cessation to achieve the desired performance outcome. However, evidence regarding peaking protocols for strength and power athletes is lacking. Current limitations for peaking maximal strength is that many stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(69 citation statements)
references
References 65 publications
(129 reference statements)
5
64
0
Order By: Relevance
“…Lastly, our results support the theoretical basis of a competitive taper. Previous research [ 60 ] has indicated that the purpose of a competitive taper is to lower fatigue while increasing readiness. This can be accomplished by reducing training volume, intensity, and possibly training cessation.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, our results support the theoretical basis of a competitive taper. Previous research [ 60 ] has indicated that the purpose of a competitive taper is to lower fatigue while increasing readiness. This can be accomplished by reducing training volume, intensity, and possibly training cessation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, performing a 1RM is considered a maximal dynamic effort. Once this value is known, programming of RT is done prescribing relative loads to the individual’s 1RM [ 14 , 15 ]. However, this methodology comes with certain disadvantages.…”
Section: The Challenges and Drawbacks Of The 1-repetition Maximum Paradigmmentioning
confidence: 99%
“…Reggiani et al [664] showed that the increase in muscle mass did not necessarily lead to increase in strength and vice versa [664], and in worst case, the increase in muscle mass was shown to decrease strength production [664,718]. There also seems to exist multiple types of muscle hypertrophy [664,820], with the concept of task-specic hypertrophy [820] becoming relevant when trying to transfer the gains from strength training program to improvements in the particular sport of the athlete [906]. For instance sports as dierent as combat sports [485,765] and ballet [16,180,818], can be beneted for similar plyometric/ballistic training for explosive force production [906] mixed with some maximum strength training.…”
Section: Precision Strength Trainingmentioning
confidence: 99%